KEDUDUKAN BARANG TITIPAN SEBAGAI AGUNAN PADA PERBANKAN SYARIAH - Muspitasari M.H; Andi Nurramadhani; Muh Fadli Mangenre (AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2022)
This study discusses the implementation of deposited goods that are used as collateral in Islamic banking, in this case trying to find the right ways to solve problems if the goods deposited are used as collateral in Islamic banking. The methodology in this study is a literature study that is narrative in nature, with a historical approach as well as looking for juridical aspects in the settlement if there is a problem with goods deposited as collateral in the transaction process carried out in Islamic banking. In this study, it is shown that the resolution of a problem can be done through deliberation and through the courts. Those who do not trust will be given a fine in the form of compensation.